Peran Komite Sekolah Di Sma Islam An-Nidhon Kecamatan Mijen-Kabupaten Demak - As’ad As’ad (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to analyze the role of school committees in An-Ndhon Islamic High School, Mijen District, Demak Regency. The research uses a qualitative approach and the method used is a case study. Data sources from the study were the head of the school committee, and the headmaster of An-Nidhom Islamic High School as the key informant (the main source) and teachers, education staff, and local community leaders as the second source. The data collection procedure is done by interview, participant observation, and document analysis related to the object of this study. Discussion of the research findings revealed that there were two quite effective roles carried out by An-Nidhom Islamic High School committee as follows: 1) Participation, 2) Supervision as a sub focus and focus of this research was the role of the school committee in An-Nidhom Islamic High School.